Persepsi Guru terhadap Model Pembelajaran Sinektik untuk Mengembangkan Keterampilan Menulis Bahasa Asing - Putri, Fika Ayu Gustiyani; Budiman, Nandang (EduInovasi: Journal of Basic Educational Studies, 2024)
The synectic learning model can enhance students’ creativity, especially in writing skills, involving the use of analogies, metaphors, and creative thinking techniques such as brainstorming. Researchers tried to examine teachers’ perceptions of synectic learning for writing skills in foreign languages through open interviews. The interview results and discussions will be presented in this article.